Signaling in a Polluted World: Oxidative Stress as an Overlooked Mechanism Linking Contaminants to Animal Communication - Marasco, Valeria; Costantini, David (Frontiers in Ecology and Evolution, 2016)
The capacity to communicate effectively with other individuals plays a critical role in the daily life of an individual and can have important fitness consequences. Animals rely on a number of visual and non-visual signals, whose production brings costs to the individual. The theory of honest signaling states that these costs are higher for low than for high-quality individuals, which prevents cheating and makes signals, such as skin and plumage colouration, indicators of individual’s quality or condition. The condition-dependent nature of signals makes them ideally suited as indicators of environmental quality, implying that signal production might be affected by contaminants. In this mini-review article, we have made the point that oxidative stress (OS) is one overlooked mechanism linking exposure to contaminants to signaling because (i) many contaminants can influence the individual’s oxidative balance, and (ii) generation of both visual and non-visual signals is sensitive to oxidative stress. To this end, we have provided the first comprehensive review on the way both non-organic (heavy metals, especially mercury) and organic (persistent organic pollutants) contaminants may influence either OS or sexual signaling. We have also paid special attention to emerging classes of pollutants like brominated flame-retardants and perfluoroalkoxy alkanes in order to stimulate research in this area. We have finally provided suggestions and warnings for future work on the links among OS, sexual signaling and contaminant exposure.